Textile additive manufacturing: An overview. Issue 1 (31st December 2022) - Keefe, Edmund M.; Thomas, Jack A.; Buller, Gary A.; Banks, Craig E.
Abstract: Additive manufacturing (3D-printing) is a rapidly emerging technology grouped under the heading of Industry 4.0 and revolutionises the way products are created. One emerging area is textiles (apparel) where additive manufacturing allows the rapid fabrication of products that are not easily produced using traditional manufacturing approaches. In this review, we provide an overview of recent developments in textile additive manufacturing highlighting this exciting and rapidly growing research area and offer insights into the future perspectives of this promising and innovative technology.